Gluten contamination in oat varieties and gluten-free oat-only products from them - Atasoy, Guler; Kahraman, Turhan; Turhan, Mahir (Food Science and Technology, 2025)
Gluten contamination from wheat, rye, and barley was examined in oats at initial and final stages of the production-consumption line, i.e., in seed form in field and processed, packaged form in market. The study focused on 23 oat seed varieties and 15 gluten-free oat-only products from these seeds. The oat seeds included all varieties registered in Turkey (23), cultivated in an experimental field during 2021–2023 growing seasons and harvested. 15 gluten-free oat-only products represented all such products available on market. A gluten-free protocol was followed throughout harvesting, handling, and analysis processes. Contamination levels in samples were determined using R5 antibody-based sandwich ELISA method, based on 5 ppm and 20 ppm gluten concentration limits. None of oat seeds had a gluten concentration greater than 5 ppm. However, 11 of 15 gluten-free oat-only products (73%) had a gluten concentration greater than 5 ppm, and 10 gluten-free oat-only products (67%) had a gluten concentration greater than 20 ppm. The contamination rate in seeds was significantly lower than global average, while in gluten-free oat-only products, it was considerably higher. This trend reflects the high prevalence of contamination worldwide in both oat seeds and gluten-free oat-only products, with contamination rate being higher in gluten-free oat-only products, suggesting that increased interventions lead to higher contamination levels.